Simvastatin induces the apoptosis of normal vascular smooth muscle through the disruption of actin integrity via the impairment of RhoA/ Rac-1 activity - Kang, Seojin; Kim, Keunyoung; Noh, Ji-Yoon; Jung, Yeryeon; Bae, Ok-Nam; Lim, Kyung-Min; Chung, Jin-Ho (Thrombosis and Haemostasis, 2016)
Statins, lipid-lowering agents for the prevention of atherosclerosis and fatal coronary heart diseases, have pleiotropic modalities on the function and physiology of vascular smooth muscle that include anti-contractile and pro-apoptotic effects. These effects were suggested to stem from the inhibition of small GTPase Rho A, but they are largely regarded as distinct and unrelated. Recently, we discovered that simvastatin causes both contractile dysfunction and apoptosis of vascular smooth muscle cells (VSMCs), reflecting that they may be closely related, yet their connecting link remains unexplained. Here, we elaborated the mechanism underlying simvastatin-induced apoptosis of normal VSMCs in connection with contractile dysfunction. Repeated oral administration of simvastatin to rats in vivo resulted in contractile dysfunction and apoptosis of vascular smooth muscle, of which pattern was well reproduced in rat VSMCs in vitro. Of note, contractile dysfunction and apoptosis occurred in concerted manners both in vivo and in vitro in the aspects of time course and dose of exposure. In rat VSMCs, simvastatin impaired the activation of small GTPases, RhoA along with Rac-1, which resulted in the disruption of actin integrity, a pivotal factor both for the generation of contractile force and survival of VSMCs. In line with the disruption of actin integrity, Bmf, a pro-apoptotic factor bound to intact actin, dissociated and translocated into mitochondria, which corresponded well with the dissipation of mitochondrial membrane potential, caspase-3 activation and ultimately apoptosis. These events were all rescued by an actin stabilisation agent, jasplakinolide as well as geranylgeraniol, indicating that damages of the actin integrity from disrupted activation of RhoA/ Rac-1 lies at the center of simvastatin-induced contractile dysfunction and apoptosis in vascular smooth muscle.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Statin; smooth muscle cells; VSMC; apoptosis